Pulmonary valve prostheses: patient's lifetime procedure load and durability. Evaluation of the German National Register for Congenital Heart Defects. (26th August 2021) - Boethig, Dietmar; Avsar, Murat; Bauer, Ulrike M M; Sarikouch, Samir; Beerbaum, Philipp; Berger, Felix; Cesnjevar, Robert; Dähnert, Ingo; Dittrich, Sven; Ewert, Peter; Haverich, Axel; Hörer, Jürgen; et al.
Abstract: : OBJECTIVES: We evaluated 4384 procedures performed between 1957 and 2018, collected in the National Register for Congenital Heart Defects, conducted on 997 patients with 1823 pulmonary valve replacements (PVRs), including 226 implanted via catheter [transcatheter valve (TCV)]. Main study targets are as follows: TCV benefit, valve type durability, decade-wise treatment changes and procedure frequencies over the lifetime of a PVR patient. METHODS: We studied TCV impact on surgical valve replacement (via Kaplan–Meier); pulmonary valve type-specific performance (Kaplan–Meier and Cox regressions with age group as stratification or ordinary variable); procedure interval changes over the decades (Kaplan–Meier); procedure load, i.e. frequency of any procedure/surgical PVR/interventional or surgical PVR by patient age (multistate analyses). RESULTS: TCV performance was equivalent to surgical PVRs and extended durability significantly. Homografts were most durable; Contegras lasted comparably less in older; and Hancock devices lasted less in younger patients. Matrix P -valves showed poorer performance. Age group stratification improves the precision of valve-specific explantation hazard estimations. The current median interval between procedures is 2.6 years; it became significantly shorter in most age groups below 40 years. At 30 years, 80% of patients had undergone ≥3 procedures, 20% ≥3 surgical PVRs and 42% ≥3 surgical or interventional PVRs. CONCLUSIONS: TCVs doubled freedom from explantation of conventional valves. Homografts' age group-specific explantation hazard ratio was lowest; Matrix P 's hazard ratio was highest. Age-stratified Cox regressions improve the precision of prosthesis durability evaluations. The median time between procedures for PVR patients shortened significantly to 2.6 years. At 30 years, 42% had ≥3 PVRs. Abstract : Pulmonary valve (PV) replacement (PVR) in patients with congenital heart defects (CHD) is performed ∼700 times per year in Germany [1].